Alleviation of aluminum toxicity in an acid sulfate soil in Malaysia using organic materials - Muhrizal, S.; Shamshuddin, J.; Husni, M. H. A.; Fauziah, I. (Taylor and Francis Group, 2003)
In Peninsular Malaysia, acid sulfate soils are commonly distributed in the coastal plains. Some of these soils are planted to crops, but the yield, which is attributed to soil infertility related to aluminum (Al) toxicity. For acid sulfate soils, liming to eliminate Al toxicity is not practical. Application of organic materials to overcome the Al toxicity is considered a better option. Research conducted to determine the efficacy of organic matter to ameliorate acid sulfate soil infertility is few. Hence, this study was carried out. The results showed that Al was reduced substantially by addition of organic materials especially green manure and green manure in combination with peat. The mixture of peat and organic materials significantly lowered total and monomeric Al concentrations. Peat mixed with organic materials (especially green manure and rice straw) synergistically promoted complexation and chelation of monomeric Al, presumably forming Al–organic acid complex in the soil. The relative root length (RRL) of mungbean was negatively correlated with various Al indices. The RRL of mungbean increased with decreasing total and monomeric Al concentration, Al3 + activities, monomeric Al activities, [Al3 + + AlOH2 + + Al(OH)2 +], [3Al3 + + 2AlOH2 + + Al(OH)2 +], aluminum activity ratio (AAR) and Al activity equivalent ratio (AER). The monomeric Al activities and Al3 + activities to maintain 90% RRL were respectively 1.21 and 0.35 µM.